1997
DOI: 10.1046/j.1365-2249.1997.d01-892.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased proinflammatory cytokine gene expression in the colonic mucosa of coeliac disease patients in the early period after gluten challenge

Abstract: Activation of T cells in the intestinal mucosa in response to gluten exposure is thought to play a key role in the pathogenesis of coeliac disease. Moreover, the response of the rectal mucosa to gluten challenge has been considered a useful predictor of gluten sensitivity in coeliac disease. In the present study, we assessed early changes in the expression of proinflammatory cytokine genes and the T cell receptor (TCR) Vβ repertoire in the rectal mucosa of coeliac disease patients following experimental gluten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 35 publications
(59 reference statements)
1
15
0
3
Order By: Relevance
“…T h -2 cytokines (IL-4, IL-6, and IL-10) were also elevated in patients with ACD, RCD, and those on GFD. The role of these cytokines in CD pathogenesis is not well understood, but immune regulatory functions at the mucosal level have been suggested [18]. The role of IL-4 remains unclear and prior studies have indicated that it may not be involved in the pathogenesis of CD [37].…”
Section: Discussionmentioning
confidence: 99%
“…T h -2 cytokines (IL-4, IL-6, and IL-10) were also elevated in patients with ACD, RCD, and those on GFD. The role of these cytokines in CD pathogenesis is not well understood, but immune regulatory functions at the mucosal level have been suggested [18]. The role of IL-4 remains unclear and prior studies have indicated that it may not be involved in the pathogenesis of CD [37].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Chowers et al [73] found that the mucosal mRNA levels for several proinflammatory cytokines increased many 1000-fold following in vivo challenge of rectal mucosa with gluten in coeliac patients, while very little IFN-␥ expression was seen initially. Therefore, the characteristic Th1 response to gliadin peptides and other prolamins may develop subsequently only in genetically susceptible individuals [5,29]; via cell-mediated mechanisms this chronic adaptive response will promote crypt hyperplasia and contribute to the villous atrophy (Fig.…”
Section: Putative Disease-initiating Role Of Proinflammatory Humoral mentioning
confidence: 99%
“…ARNm: EC actividad = normal Normal: expresión en el epitelio (sobretodo en la punta de las vellosidades Valores proteína: EC actividad > normal 19,29,31,34 y poco en las criptas) y en la lámina propia (especialmente en las zonas próximas al epitelio) EC actividad: ligera disminución en el epitelio, aumento en lámina propia (región subepitelial) 33,34 TNFα EC actividad = normal Normal: expresión en la lámina propia, no en el epitelio Valores proteína: EC actividad > normal 19,28,29,35 EC actividad: aumento en la lámina propia, no aparece en el epitelio 32,33 Aumento Hay aumento en los valores de proteína activa sin cambios EC actividad: expresión en pocas células mononucleares de la lámina propia 37 , en el ARNm debido a regulación postranscripcional 28,37 o aumento importante en la lámina propia y en los enterocitos 28 …”
Section: Expresión De Citocinas En La Mucosa Intestinal De Pacientes unclassified
“…No se ha conseguido demostrar un incremento en los valores de ARNm de TNFα cuando se estudia la biopsia completa de pacientes con EC en actividad 19,28 o poblaciones de linfocitos T aislados de estas biopsias 29 . En algún caso, no se detecta el aumento de ARNm de TNFα en biopsias tras la instilación de péptidos de gluten directamente por vía rectal 35 . Sin embargo, en otro estudio sí se ha detectado un aumento de la expresión de ARNm de TNFα tras la estimulación in vitro de biopsias intestinales 19 .…”
Section: Il-10unclassified
See 1 more Smart Citation